Training on TOEFL Exam Success Strategy for PPG Teachers of English Subject in Central Java - Haryanto Haryanto; Sindy Alfiani Novita (Salus Publica: Journal of Community Service, 2023)
This Community Service activity aims to increase the proficiency of PPG English teachers in finishing the TOEFL-based English test questions.  To achieve this goal the methods in implementing this activity is through Webinar and training with a combination of theory and practice as well as discussion and performance of the results of the training at the end of the activity. The result of implementing this activity is that TOEFL-based English training is one of the efforts that can be made to improve English mastery skills for teachers, participants benefit from knowledge about the theoretical basis, principles, and strategies of the TOEFL test and its grid so that it better equips the students' teachers in dealing with TOEFL-based English questions, as well as improving the English language skills of teachers in general. Moreover, the results of this activity can be used as material for consideration in making policies related to improving the quality of teachers in their respective schools